2021
DOI: 10.1111/gcb.15731
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil organic carbon stock to animal manure application: A new global synthesis integrating the impacts of agricultural managements and environmental conditions

Abstract: Enhancing soil organic carbon (SOC) through applying animal manure is of interest for both sustaining cereal production and mitigating greenhouse gas (GHG) emissions.Previous syntheses showed that manuring-induced SOC changes varied substantially with agricultural managements and environmental conditions, while their significance and relative importance to such variability are still largely uncertain. Here, we presented a new synthesis using an updated and balanced database integrating the manuring-induced SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…The increase in the TN may be partially related to the biological N 2 fixation of the legume crops (pea). In addition, the SOC, TN, and MBC could be significantly increased by applying manure compared with applying no fertilizer or mineral fertilizer alone [5,49]. The application of manure affects the structure and composition of the microbial community, such as bacterial and fungal abundances [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the TN may be partially related to the biological N 2 fixation of the legume crops (pea). In addition, the SOC, TN, and MBC could be significantly increased by applying manure compared with applying no fertilizer or mineral fertilizer alone [5,49]. The application of manure affects the structure and composition of the microbial community, such as bacterial and fungal abundances [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing soil to such a matrix medium of course is a brute, but for greenhouses apparently feasible simplification (Figure a). For farmland with its alternating climate, water, and light conditions and based on the above quoted observation that sustained fertility goes strictly with soil carbon content, people can differentiate essentially three anthropogenic approaches: (i) addition of manure and waste biomasses, , (ii) biochar addition, and (iii) natural and artificial humic substances (Figure b).…”
Section: Soils In the Anthropocenementioning
confidence: 99%
“…Studies have shown that the quantity and quality of SOM following N enrichment were linked with soil microbial communities and the associated enzyme activities (Craine et al, 2007). The organic fertilizer is known to enhance SOM and improve soil fertility (Li et al, 2021). A recent study indicated that the carbon loss under alpine permafrost deterioration is linked to decreasing microbiological stability (Wu et al, 2021).…”
Section: Combined Fertilization Leads To Higher Microbial Network Sta...mentioning
confidence: 99%